Carcinosarcoma of Vater’s papilla: case report of a rare neoplasm and review of the literature - Rumi Itoyama; Yo-ichi Yamashita; Yosuke Nakao; Toshihiko Yusa; Naoki Umezaki; Takanobu Yamao; Shigeki Nakagawa; Hirohisa Okabe; Katsunori Imai; Hiromitsu Hayashi; Daisuke Hashimoto; Akira Chikamoto; et al. (Surgical Case Reports)
Abstract Background Carcinosarcoma is a rare tumor that includes both carcinoma and sarcoma components. It develops commonly in the female reproductive tract, most often in the uterus. However, as there are a small number of similar cases in the English literature, we would like to present a rare case of a carcinosarcoma in Vater’s papilla. Case presentation A 76-year-old female patient was preoperatively diagnosed with a papillary adenocarcinoma in Vater’s papilla by endoscopic biopsy. The patient underwent subtotal stomach-preserving pancreaticoduodenectomy, and postoperative pathological examination diagnosed the carcinosarcoma. The patient received adjuvant chemotherapy with gemcitabine, but multiple liver metastases were found 3 months after the operation. Though chemotherapy with gemcitabine and cisplatin was introduced, she died owing to tumor progression 7 months after the operation. Conclusion Because carcinosarcoma of Vater’s papilla is a rare disease, a suitable treatment strategy has been unclear. We also present a review of the English literature regarding carcinosarcoma of Vater’s papilla.